Spatial and Chemical Complexity in the W75N Star-forming Region - Morgan M. Giese; Will E. Thompson; Dariusz C. Lis; Susanna L. Widicus Weaver (The Astrophysical Journal)
We present the analysis of NOEMA interferometric observations of the high-mass star-forming region W75N(B) with a focus on molecular composition and distribution of prebiotic molecules in the source’s multiple cores. Over 20 molecules are identified across the region, with many being fit for column density, rotational temperature, spectral line FWHM, and v _lsr . This work includes the first known detection and initial analysis of complex organic molecules in the MM2 and MM3 regions. Furthermore, parameter maps were created from the six molecules that were well fit across multiple regions. The molecular emission was imaged and correlated across different molecules and the continuum to reveal structural features. From the spatial and spectral analysis of the MM1 region, these results concur with those from other studies showing that there is a difference in chemical composition between the MM1a and MM1b regions, with sulfur-bearing molecules tracing MM1a and organic molecules tracing MM1b. The molecular emission imaged toward the MM3 region reveals two peaks, possibly indicating the presence of multiple young stellar objects. These results provide detailed quantitative information about the physical parameters and distributions of molecules in this source. Additionally, these results are part of a follow-up of a single-dish survey of multiple star-forming regions and are discussed in this context.